Algal Response Based on in situ Experiments of Nutrients Enrichment Bioassays in Lake Chaohu (China). Issue 2 (September 2019) - Fu, Xuemei; Zheng, Mingxia; Su, Jing; Sun, Yuanyuan; Zhang, Rui; Wang, Kun; Feng, Xuehua; Ji, Danfeng; Zhuo, Feng
Abstract: The algal response in relation to nutrient condition changes as well as environmental factors in Lake Chaohu (China) was investigated by in situ experiments of nutrients enrichment bioassays (NEBs) in this study. The results showed that both N and P enrichement could significantly inspire the algal growth especially in July. The highest relative algal growth coefficient compared with control obtained at TN/TP ratio of 10 reached 270% and 163% with respect to Chl-a and algal cell density, respectively. It indicated that algae blooms in Lake Chaohu are prone to occur at the TN/TP ratio around 10:1, which can be an early-warning indicator of algal blooms in Lake Chaohu. Furthermore, besides the nutrient conditions, the algal growth was significantly affected by environmental parameters such as water temperature and dissolved oxygen, which may also act as a trigger of algal blooms. This study suggested an alternative early-warning prediction method for algal blooms and provided basic information for eutrophication management scheme for Lake Chaohu.